PERLINDUNGAN HUKUM TERHADAP PEMEGANG KARTU KREDIT PT. BANK NEGARA INDONESIA (PERSERO) TBK CABANG SUDIRMAN PEKANBARU DITINJAU DARI UNDANG-UNDANG NO. 8 TAHUN 1999 TENTANG PERLINDUNGAN KONSUMEN - Bachtiar, Maryati (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2015)
This study concludes that the basic legal relationship between credit cardholders with the issuing bank is an agreement that can be classified as a raw deal,because the document containing the clause agreement has been prepared anddetermined in advance by the publisher, in this case the bank, as the lender thataccepts only credit card holders or not against all clauses specified (take it orleave it). In the agreement contained in the rights and obligations for banks andcredit card holders. Liabilities of the bank are entitled to the credit card holders,and conversely the right bank is a liability for credit card holders. The rights andobligations of the parties are constrained by the presence of Act No. 8 of 1999 onConsumer Protection is based on five (5) principles that benefit, justice, equity,security and consumer safety, and legal certainty.The credit card customers law protection can only be realized with theparticipation of the various parties. The credit card customers should be moreproactive to know their rights and also their obligations and for the bankspreferably was open and give more explanation during the hand marker theapplication of credit card. With the existence of the balanced condition both fromthe bank and the customer than the protection will run as expected. Although rightnow the government already gave a new regulation no. 11 of 2003 on Informationand Electronic Transactions, but in fact the role of the Law is felt not efficient. Itwas felt not enough to protect the public and interested parties, still needed morerepresentative formulation that can reach all forms of crime by using a credit cardKeyword : Customers Law Protection – Credit Card